A gender based analysis of language use and self-presentation on Facebook / Hou Yunjuan - Hou, Yunjuan (2014)
Today more and more people use social networking sites for the purpose of communication. For example, in Malaysia, Facebook is the most popular website and it has become an inseparable part of people‘s lives (Malaysian Website Rankings for March 2012). According to Malaysia Facebook Statistics (2012), there are 13,154,060 Facebook users in Malaysia, where 54% are males and 46% are females. In this virtual space, males and females can present themselves in a multitude of ways when they communicate with each other. This study on the one hand aims to examine the language used by both males and females in tandem with the kind of linguistic features. On the other hand, this study also attempts to examine how male and female Malaysian Chinese undergraduates present themselves through language use on Facebook. In concurrence with the research aims and research questions of this study, a qualitative approach has been employed. The finding in language use showed that female Facebook users used more linguistic features than males in the status updates and feedback of their Facebook homepages except for certain aspects such as hedges, initial adverbs and Malaysian Chinese English particles. With respect to self-presentation, the finding revealed that males and females presented themselves more similarly except in the aspect of the emoticon use. Communication is a highly important element in relationship establishment especially between males and females. Armed with the knowledge of language to be used and knowledge of online self-presentation, Malaysian Chinese male and female undergraduates can learn how to use appropriate language to typify their online respective gender identities and to further improve their online communication skills.